2016
DOI: 10.1002/jcph.804
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Compounds Exhibiting Target-Mediated Drug Disposition (TMDD): A Minireview

Abstract: Nonlinearities are commonplace in pharmacokinetics, and 1 special source is the saturable binding of the drug to a high-affinity, low-capacity target, a phenomenon known as target-mediated drug disposition (TMDD). Compared with large-molecule compounds undergoing TMDD, which has been well recognized due to its high prevalence, TMDD in small-molecule compounds is more counterintuitive and has not been well appreciated. With more and more potent small-molecule drugs acting on highly specific targets being develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Although the concept of TMDD was raised by Levy 25 years ago based on the unusual nonlinear pharmacokinetics of a number of small-molecule drugs, TMDD only became a widelyknown concept with the proliferation of large-molecule biologics because numerous protein drugs demonstrate nonlinear pharmacokinetics imparted by TMDD due to their specific binding to their pharmacological targets (Levy, 1994;Dua et al, 2015). Due to the relatively low prevalence of TMDD in small-molecule drugs, it has been an overlooked area (An, 2017;van Waterschoot et al, 2018), misunderstanding has evolved that "TMDD cannot occur in small-molecule compounds". This is a clear misconception and our study has provided direct evidence that TMDD can occur in small-molecule compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of TMDD was raised by Levy 25 years ago based on the unusual nonlinear pharmacokinetics of a number of small-molecule drugs, TMDD only became a widelyknown concept with the proliferation of large-molecule biologics because numerous protein drugs demonstrate nonlinear pharmacokinetics imparted by TMDD due to their specific binding to their pharmacological targets (Levy, 1994;Dua et al, 2015). Due to the relatively low prevalence of TMDD in small-molecule drugs, it has been an overlooked area (An, 2017;van Waterschoot et al, 2018), misunderstanding has evolved that "TMDD cannot occur in small-molecule compounds". This is a clear misconception and our study has provided direct evidence that TMDD can occur in small-molecule compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Among all small-molecule drugs that were reported to exhibit TMDD, only vildagliptin is metabolized by its pharmacologic target, DPP-4. 23 Considering the low frequency of drug-target complex degradation in small-molecule compounds, in our model there is no additional elimination process for the drug-target complex. Furthermore, we assume that the drug has no nonspecific binding to plasma proteins, such as albumin and alpha-acid glycoprotein, and there is no rate-limiting factor in the distribution of drug between plasma and tissue.…”
Section: Small-molecule Compounds With Saturable Binding Tomentioning
confidence: 99%
“…[16][17][18][19][20][21][22] We have provided an overview of TMDD in smallmolecule compounds in a recent mini-review article and listed the individual small-molecule drugs that have been reported to exhibit TMDD. 23 TMDD in smallmolecule compounds could be caused by saturable binding to targets located in tissues and/or plasma. Depending on the location of the binding targets, the behavior of nonlinear pharmacokinetics imparted by TMDD could be very different among various small-molecule compounds.…”
mentioning
confidence: 99%
“…The TMDD approach for a single drug finds broad application in PK modeling, see [4, 5] for a list of compounds. TMDD behavior is used in several scenarios, such as binding of one drug to two targets [6], for antibody-drug conjugates [7], or receptor mediated endocytosis [8], just to name a few.…”
Section: Introductionmentioning
confidence: 99%